The Benefits of Sequential Screening - Daniel Krähmer; Roland Strausz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2011)
This paper considers the canonical sequential screening model and shows that when the agent has an expost outside option, the principal does not benefit from eliciting the agent's information sequentially. Unlike in the standard model without expost outside options, the optimal contract is static and conditions only on the agent's aggregate final information. The benefits of sequential screening in the standard model are therefore due to relaxed participation rather than relaxed incentive compatibility constraints. We argue that in the presence of expost participation constraints, the classical, local approach fails to identify binding incentive constraints and develop a novel, inductive procedure to do so instead. The result extends to the multi-agent version of the problem.
urn:nbn:de:bvb:19-epub-13191-4
Keywords: D82; H57; 330; Sequential screening; dynamic mechanism design; participation constraints; Mirrlees approach; Vertrag; Informationswert; Signalling; Prinzipal-Agent-Theorie